RENDAHNYA TINGKAT OBJEKTIVITAS PEMBERITAAN SEPUTAR AGAMA DAN UMAT KRISTEN PADA ERAMUSLIM.COM - Suliana Khusnulkhatimah (Program Studi Ilmu Komunikasi FISIP Universitas Sultan Ageng Tirtayasa, 2022)
In a news, the facts presented by the media are second-hand reality and can be vulnerable to media agenda intervention. In the end, agenda media capable to separates the fact reconstruction process from journalistic procedures: the principle of objectivity. As a mass media with an Islamic supremacy viewpoint, Eramuslim.com often discusses religious sentiments through its news coverage, especially towards Christianity and its people. Eramuslim.com was even blocked by the Kementrian Komunikasi dan Informatika (Kominfo) twice, in March 2015 and January 2016, because it was considered as a site that supports radicalism or radicalism sympathizers. This research is based on agenda setting theory, and the concept of media objectivity. The research is based on a quantitative approach, with content analysis methods. The results shows, the level of objectivity of news related to Christianity published by Eramuslim.com during January 28, 2016 to May 24, 2021 was low. Only 3 news or 1.8% news of the 169 news researched, met the principle of objectivity.